Dual Measures of Monopoly and Monopsony Power: An Application to Regulated Electric Utilities - Atkinson, Scott E.; Kerkvliet, Joe (The Review of Economics and Statistics, 1989)
Scott E. Atkinson, Joe Kerkvliet, Dual Measures of Monopoly and Monopsony Power: An Application to Regulated Electric Utilities, The Review of Economics and Statistics, Vol. 71, No. 2 (May, 1989), pp. 250-257